Temporal measurements for Second Language speaking fluency - Qurbi, Essa (Lesya Ukrainka Volyn National University, 2024)
This study investigates the relationship between temporal measurements and second language (L2) speaking fluency, focusing on speech rate, mean length of utterance, and pausing patterns. The study recruited 60 advanced English L2 adult learners (male and female) who were presented with a picture book where each page included only one picture representing a specific sequence of the story's development. The participants’ main task was to orally describe the story where their oral descriptions were electronically recorded using PsychoPy software. The primary goal was to determine which of the above-mentioned temporal measurements significantly influence L2 speaking assessment. These participants’ spoken samples were evaluated by five English language instructors using standardized L2 speaking assessment rubric. A statistical analysis of was conducted to examine the effect of these three temporal measurements on L2 speaking assessment. The results showed that average words per minute and average pause duration per minute, but not mean length of utterance, were significant factors of L2 speaking fluency assessment. However, the interaction between these factors was not significant. That is, average words per minute and average pause duration per minute factors provide a listener with a positive impression about L2 speakers’ speaking performance. These results are consistent with other studies that examined L2 speaking fluency. The findings also underline the importance of listeners’ impression when it comes to L2 speaking assessment. In addition, the study highlights the effect of temporal measurements on L2 speaking assessments and provides insights for both evaluators and learners on the factors affecting L2 fluency assessment.
Keywords: speech rate; L2 speaking assessment; L2 fluency; temporal measurements; pausing patterns; mean length of utterance